Longitudinal decline in lung function: a community-based cohort study in Korea - Leem, Ah Young (Sci Rep, 2019)
Progressive decline in lung function is the hallmark of chronic obstructive pulmonary disease (COPD). We aimed to assess the rate of decline in forced expiratory volume in 1 second (FEV(1)) in patients from a community cohort database in Korea. 5,865 subjects aged 40–69 years from the Ansung-Ansan cohort database I–III (2001–2006) were included in this study. We assessed the annual rate of decline in FEV(1) over time in relation to smoking status, patient sex, and presence or absence of pre-bronchodilator airflow limitation using a generalized additive mixed model. The mean follow-up duration was 3.8 years. The annual mean decline in FEV(1) in the entire cohort was significantly more rapid for men than women (31.3 mL vs 27.0 mL, P = 0.003). Among men without pre-bronchodilator airflow limitation, annual mean declines in FEV(1) were 31.5, 35.5, and 40.1 mL for never smokers, former smokers (P = 0.09 vs. never smokers), and current smokers (P < 0.001 vs. never smokers), respectively; and 23.4, 19.7, and 33.9 mL, respectively, for men with pre-bronchodilator airflow limitation. Thus, among Korean males, smoking accelerates lung function decline over time whereas smoking cessation slows the rate of FEV(1) decline regardless of pre-bronchodilator airflow limitation. This underscores the importance of smoking cessation in Koreans.